2022
DOI: 10.1071/py21162
|View full text |Cite
|
Sign up to set email alerts
|

Implications of telehealth services for healthcare delivery and access in rural and remote communities: perceptions of patients and general practitioners

Abstract: Background Accelerated by the coronavirus disease 2019 (COVID-19) pandemic, Australia has shifted towards greater use of telehealth to deliver care for rural and remote communities. This policy direction might risk a shift away from the traditional model of informed person-centred care built around care relationships to a technology-mediated health transaction. Potential opportunity costs of widespread telehealth services on the quality of care for rural and remote communities remain understudied. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This study explored the impact of the initial COVID-19 response on the delivery of primary care in a remote First Nations community, and it highlights the importance of a case management-based model in this setting. The significant reduction in primary care presentations observed during and immediately after the initial COVID-19 restrictions was expected and has been observed in other studies in non-Indigenous settings (Sumner et al 2022). The findings from this study suggest the reduction in the number was not a result of reduced service availability compared with the same period in 2019.…”
Section: What Can Be Learnt From the Casesupporting
confidence: 83%
See 1 more Smart Citation
“…This study explored the impact of the initial COVID-19 response on the delivery of primary care in a remote First Nations community, and it highlights the importance of a case management-based model in this setting. The significant reduction in primary care presentations observed during and immediately after the initial COVID-19 restrictions was expected and has been observed in other studies in non-Indigenous settings (Sumner et al 2022). The findings from this study suggest the reduction in the number was not a result of reduced service availability compared with the same period in 2019.…”
Section: What Can Be Learnt From the Casesupporting
confidence: 83%
“…Despite the PHCC of interest remaining open, public health and community messaging were urging people to 'stay at home' and this likely influenced people to delay non-urgent appointments regardless of baseline health status. As identified by Sumner et al (2022), it is likely that fear of contracting COVID-19 and uncertainty of treatment and prognosis was a factor in reduced healthcareseeking behaviour. Additional public health screening procedures and misinformation about COVID-19 may also have been an influencing factor in people limiting their engagement with primary care services (Pickles et al 2021).…”
Section: What Can Be Learnt From the Casementioning
confidence: 99%
“…Overall, in most of the studies, participants reported positive aspects of video consultations. The exception was Sutarsa et al (2022) who found that they were distant and lacking in personal touch or ability to form a deeper caring relationship between the patient and clinician. They warned that replacing face-to-face with video consultations could lead to a loss of trust and continuity of care.…”
Section: What Current Research Tells Usmentioning
confidence: 99%
“…In terms of service implementation, these elements are important but do not outline the broader implementation factors critical to the success of telehealth delivery in rural areas. One study by Sutarsa et al explored the implications of telehealth as a replacement for face-to-face services from the perspectives of general practitioners and clients (7) and articulated that telehealth services are not a like-for-like service compared to face-to-face modes.…”
Section: Introductionmentioning
confidence: 99%